Створення виробничого об'єднання "Запоріжтрансформатор" - класика жанру. (Zaporizhzhia Historical Review, 2021)
The article deals with establishment of manufacturing company ”Zaporizhtransformator” in 1971. It was a great event in the development of Zaporizhzhia industrial complex as a whole and in electroengineering industry in particular.